High cross wind gust loads on ground vehicles from moving model experiments - Humphreys, Nicholas David. (1995)
The environmental wind tunnel at Nottingham University has been extended so that realistic mean hourly atmospheric boundary layers can be generated at sufficient scale to allow aerodynamic tests of sharp edged vehicles to be undertaken.